PENGEMBANGAN PADI HIBRIDA: PENGALAMAN DARI ASIA DAN PROSPEK BAGI INDONESIA (Forum Penelitian Agro Ekonomi, 2024)
Food security always occupies top government’s priority in national development due to its huge impact in terms of social, economy, and politics of the country. Regarding the strategic role of food, the policy on increasing food production and farmers' welfare constitute a crucial program, particularly in the Ministry of Agriculture. With the increased demand for food (rice) steadily as well as the rice production levelling off, the government seeks a technological breakthrough, such as hybrid rice introduction. This rice variety is expected to boost production significantly, although its role is still debatable. This paper aims to look at the potential and challenges of hybrid rice development in Indonesia as well as to describe the development in some countries as a comparative study. The result shows both theoretically and factually in some countries, the hybrid rice has a higher potential yield than non-hybrid rice as long as it meets the agronomic requirements. Nevertheless, the development of hybrids (mainly outside of China) still encounters a set of problems, i.e. unstable production, susceptibility to pests and diseases, expensive seed prices, low quality grain, and less-favored rice flavor. Specifically for Indonesia where the hybrid rice is still newly introduced, the hybrid rice development will require a well-planned, gradual, and socialization process. Mass program approaches in hybrid rice which is merely to capture the target oriented, tend to create an ineffectiveness both of output achievement and budget. Agro-ecosystem aspect and the characteristics of farmers in terms of social, economic and cultural sides become a key factor to accomplish the successful hybrid rice development in the future.